2013
DOI: 10.1007/s00381-013-2273-7
|View full text |Cite
|
Sign up to set email alerts
|

Third-ventricular neurocysticercosis: hydraulic maneuvers facilitating endoscopic resection

Abstract: Neurocysticercosis, infection of the central nervous system with the larval cysts of the pork tapeworm, Taenia solium, is the most common parasitic disease of the central nervous system. The disease is a major global cause of acquired epilepsy and may also manifest as intracranial hypertension due to mass effect from large cysts, or to cerebrospinal fluid flow obstruction by intraventricular cysts or inflammation of the subarachnoid space. While the condition is endemic in several regions of the world and has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We also conducted a literature review looking for reported cases with surgical/ histopathological confirmation of ventricular cysticercosis during the past 20 years. A total of 21 papers describing 29 patients, where case descriptions and neuroimaging findings were appropriately detailed as to apply our set to diagnostic criteria, were found [35,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Despite the fact that most of these patients did not had a serum EITB performed, the set allowed a definitive pre-operative diagnosis of NCC in 23 cases (one absolute criterion in 12, two major neuroimaging in six, and one major neuroimaging plus one confirmative in five), and a probable diagnosis in the remaining six patients.…”
Section: Additional Evaluationsmentioning
confidence: 99%
“…We also conducted a literature review looking for reported cases with surgical/ histopathological confirmation of ventricular cysticercosis during the past 20 years. A total of 21 papers describing 29 patients, where case descriptions and neuroimaging findings were appropriately detailed as to apply our set to diagnostic criteria, were found [35,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Despite the fact that most of these patients did not had a serum EITB performed, the set allowed a definitive pre-operative diagnosis of NCC in 23 cases (one absolute criterion in 12, two major neuroimaging in six, and one major neuroimaging plus one confirmative in five), and a probable diagnosis in the remaining six patients.…”
Section: Additional Evaluationsmentioning
confidence: 99%
“…Intraventricular cysts in the lateral and third ventricles can be removed with an endoscopic approach which allows for simultaneous resection of the lesion and complements with CSF diversion via ventriculostomy [17,18]. A simple hydraulic maneuver by placing the patient in the Trendelenburg position intraoperatively can facilitate the endoscopic en bloc removal of third ventricular neurocysticercosis [20]. Cysts in the fourth ventricle can by removed from a posterior approach, either with neuroendoscopy or microdissection [17,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%